Penerapan TPACK dan Problem-Based Learning Model untuk Meningkatkan Kemampuan Berpikir Kritis Siswa - Nurul Ayuni; Cut Morina Zubainur; Taufik Fuadi Abidin (Universitas Syiah Kuala, 2020)
Students' low critical thinking skills were due to the lack of teachers' ability to foster it during the learning process. This research applied the TPACK teaching tools framework with problem-based learning in the mathematics classroom to examine and develop the level of critical thinking skills of Year 10 students at one of the senior high schools in Banda Aceh, Indonesia. The research instrument was formative tests given at the end of the lessons. The students' test showed that there was a lack of critical thinking skills at the beginning of the lesson. The last test showed that tificant positive development toward the level of students' critical thinking skills during the learning process using the TPACK learning framework with the problem-based learning model.